Simulation and optimization of a modified salt extractive distillation process for the production of anhydrous ethanol - Manish Kumar Yadav; Saumya Agarwal; Shilpi Verma; Vimal Chandra Srivastava; Urška Lavrenčič Štangar; Praveen Kumar (Results in Chemistry)
Producing anhydrous ethanol through ethanol dehydration is challenging due to the formation of an ethanol-water azeotrope. Traditional methods use carcinogenic liquid separating agents like benzene to break this azeotrope. This study introduces a modified salt extractive distillation technique using soluble calcium chloride to produce anhydrous ethanol more safely and efficiently. We conducted simulations and optimizations of this new method, with columns operating under 80 % flooding conditions. This process demonstrated an effective energy consumption of 5.25 MJ per kg of ethanol, significantly lower than traditional methods. The innovative approach uses minimal calcium chloride and operates at reduced reflux flow rates, leading to smaller column diameters. Moreover, the energy needed for recovering the salt solution is just 4.4 % of the total energy consumption. Comparisons with existing literature show that our method's energy use is the lowest reported, marking a significant advancement in eco-friendly ethanol production.